A trans-activating transduction peptide fused nanobody targeting viral nonstructural protein NS4B inhibits bovine viral diarrhea virus replication - Zhao, Bao; Lv, Zehao; Fan, Wenqi; Zhang, Ying; Wei, Shuang; Fang, Junyang; Huang, Ni; Chen, Xiwen; Wang, Lizhen; Qi, Xuefeng (Frontiers in Immunology, 2025)
IntroductionBovine viral diarrhea virus (BVDV) is a major pathogen in cattle globally. Nanobodies (Nbs) possess attractive therapeutic properties, but their efficacy against intracellular targets like BVDV is hindered by poor membrane permeability.MethodsA nanobody (Nb91) targeting the BVDV nonstructural protein NS4B was isolated. Nb91 was intracellularly expressed to assess its antiviral effect. Furthermore, Nb91 was fused to the cell-penetrating TAT peptide to generate TAT-Nb91. The internalization efficiency of TAT-Nb91 and its inhibitory effects against both cytopathogenic (CP) and noncytopathogenic (NCP) BVDV biotypes were evaluated in MDBK cells and in bovine endothelial (Bend) cells, the primary in vivo targets of BVDV. The epitope of Nb91 on NS4B was mapped.ResultsIntracellularly expressed Nb91 potently suppressed BVDV replication in MDBK cells ( 100% inhibition). TAT-Nb91 was effectively internalized in a dose- and time-dependent manner. It inhibited CP and NCP BVDV replication in MDBK cells by approximately 70% and 40%, respectively, and achieved over 50% inhibition for both biotypes in Bend cells. Epitope mapping identified NS4B amino acids 328-347 as the critical binding region for Nb91.DiscussionThese findings demonstrate that a cell-penetrating nanobody targeting the conserved viral protein NS4B can effectively inhibit BVDV replication across relevant cell types and biotypes. This establishes TAT-fused nanobodies as a promising new therapeutic strategy against BVDV.